PERTIMBANGAN DAN PERMASALAHAN PEMAKAIAN ALAT INTERSEPTIK ORTODONSI SECARA DINI PADA ANAK MASA TUMBUH KEMBANG - Iwa Sutardjo RS (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2011)
Growth and development prosesses is potencially affected by serrounding environment, and easily disturbed by any foreign stimulations. Intesceptic orthodontic applinces is one of the many physical environments which have the ability to change oral cavity environment. Result of the interaction may produce a non stable or even stable effect, depanding on individual’s growth and development processes early interseptic treatment in children is adviced, it can be used to evoid dento cranial growth and development disturbances. It is recuired to understand bio-mechanic appliences system before interseptic orthodontic treatment is applied. The use of fixed or removable appliences in children requires a specifi management.